Prevalence of depression among athletes at United States International University - Africa (USIU-A) Nairobi, Kenya - Otieno, T.; Nyayieka, M. (American Journal of Sports Science, 2024)
Depression is a prevailing issue among athletes today. Studies show that globally, up to 20% of young people are affected by health issues. This study aimed at investigating the prevalence of depression among athletes at USIU-A, examining its correlation with demographic and sports-related variables. The study employed a mixed-methods approach on a sample size of 71. The study was guided by George Engel`s Biopsychosocial model and Transactional Model of Stress and Coping. The sample size was tested for depression utilizing the Beck Depression Inventory-II (BDI-II) questionnaire where data was collected to evaluate depressive symptoms among athletes. The majority of participants were aged between 21-25 years (56.3%), followed by the 26-30 age group (28.2%). In order to determine the relationship between. In order to determine the relationship between gender and sports played. Spearman Correlation Coefficient was used and the study showed weak positive association between gender and the type of sport played (r = 0.108, p = 0.372), with no statistically significant association. An assessment on the prevalence of depression and severity levels was done with 27% showing critical levels of depression. A chi square test was conducted to assess the relationship between sports played and depression. The value of the Pearson Chi-Square test statistic is 77. 938 with 40 degrees of freedom. The value of the asymptotic significance equals to. 000 which is less than the alpha value of 0. 05 which indicates there is a statistically significant relationship between the sport played and depression. These results found indicate that depression is a prevailing issue among athletes and should be addressed as a clinical concern.